If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 7x + -1 Reorder the terms: 7 + 6x = 7x + -1 Reorder the terms: 7 + 6x = -1 + 7x Solving 7 + 6x = -1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 7 + 6x + -7x = -1 + 7x + -7x Combine like terms: 6x + -7x = -1x 7 + -1x = -1 + 7x + -7x Combine like terms: 7x + -7x = 0 7 + -1x = -1 + 0 7 + -1x = -1 Add '-7' to each side of the equation. 7 + -7 + -1x = -1 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = -1 + -7 -1x = -1 + -7 Combine like terms: -1 + -7 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8
| Sin=-2 | | 14-w=17 | | cosz=-2 | | -1/2=3/5y-1/3 | | 9(3a+8)= | | cosz=-3 | | 4x^4/6/5x^3/6 | | -1/3v-1/2=-3/7 | | 12+2j=-j | | 5X=245 | | Y=-4x^2+16x-16 | | (4x+25)+x=180 | | 20+2k=-18k | | 5x+6=30+3x | | 5p^2+3=12p | | 3x^2+9x=-30 | | 5x/3+15/2=2x+10 | | -3(c+3)=4(c+3) | | 11-k=-10 | | 2(c-14)=-8 | | (4x+25)+y=180 | | x/2+1,5=6 | | y=5t+30 | | 808-m=722 | | 3(a+0.35)=1.5 | | -6n-4=2n+4(1-3n) | | -49=635-j | | 0=-16t^2+40t+6 | | 25+4x=180 | | m^8-n^8=0 | | 714=17(k-935) | | 8+3t=13-t |